Searching for Gravitational Wave Associations with High-Energy Astrophysical Transients - (:unkn) unknown (My University, 2022)
Gravitational waves (GW) have become an invaluable tool in modern astronomy, especiallyin conjunction with other astronomical observations. GWs are created in highly dynamical systems such as compact binary coalescences (CBC) which are comprised of black holes and/or neutron stars. The Laser Interferometer Gravitational Wave Observatory (LIGO), Virgo Observatory, and KAGRA have now collectively identified almost a hundred of these events. GWs have also been predicted to come from core collapse supernovae. Both of these types of systems have been shown to produce other detectable transients, such as gamma- ray bursts (GRB) and neutrino bursts. Observations of the same astrophysical system with multiple messengers are proven to be invaluable to understanding these systems and constraining crucial physical constants. Therefore, efforts to find more multi-messenger events are increasingly important as detection sensitivities and expected rates increase. It is especially important to identify multi-messenger events as soon as possible in order to alert other astronomers and to facilitate additional follow-up. In this dissertation, I describe my work in the LIGO-Virgo-KAGRA (LVK) Collaboration developing both infrastructure and techniques for multi-messenger searches involving GWs.
Keywords: gamma-rays; gravitational waves; multimessenger; neutrinos